Paridad de género o representación igualitaria en la participación política de las mujeres en el cantón Santa Elena durante el periodo 2023. - De la Cruz Borbor, María Esperanza (2024)
The main objective of this research project is to analyze the application of the gender parity law in the political participation of women in the exercise of functions as part of a center administration of city and to evaluate whether this law is an effective tool to achieve equal representation in the political sphere. comprehensively addressing the analysis of various aspects that have contributed to the formation of the current representatives in the Plenary of Santa Elena city. The research is based on a review of the academic literature related to the gender parity law, gender equality and women's political participation at the regional and national level, providing a theoretical framework that, as a set of experiences collected in relation to the trajectories of the current representatives of the territory of study, leave to the reader's perception other subtopics such as: political violence, gender-based violence, stereotyped positions, parity democracy and political parties, which are considered fundamental in the analysis and discussion of this article. The study is based on descriptive research, using a qualitative technique in which life histories of women elected from the period 2023-2027 in the Santa Elena city are collected through semi-structured interviews, in order to obtain a deep understanding from their perspectives in relation to the application of the Gender Parity Law. It provides valuable information for policymakers, advocates for women's rights, aspiring political participants supporting the importance and ongoing monitoring of the gender parity law as a key tool to achieve equal and equitable representation. Key words: peasant women, social reproduction, status of women, development, gender, parity democracy